Intrinsic stimuli‐responsive nanocarriers for smart drug delivery of antibacterial agents—An in‐depth review of the last two decades. (17th August 2020) - Devnarain, Nikita; Osman, Nawras; Fasiku, Victoria Oluwaseun; Makhathini, Sifiso; Salih, Mohammed; Ibrahim, Usri H.; Govender, Thirumala
Abstract: Antibiotic resistance due to suboptimal targeting and inconsistent antibiotic release at bacterial infection sites has driven the formulation of stimuli‐responsive nanocarriers for antibacterial therapy. Unlike conventional nanocarriers, stimuli‐responsive nanocarriers have the ability to specifically enhance targeting and drug release profiles. There has been a significant escalation in the design and development of novel nanomaterials worldwide; in particular, intrinsic stimuli‐responsive antibiotic nanocarriers, due to their enhanced activity, improved targeted delivery, and superior potential for bacterial penetration and eradication. Herein, we provide an extensive and critical review of pH‐, enzyme‐, redox‐, and ionic microenvironment‐responsive nanocarriers that have been reported in literature to date, with an emphasis on the mechanisms of drug release, the nanomaterials used, the nanosystems constructed and the antibacterial efficacy of the nanocarriers. The review also highlights further avenues of research for optimizing their potential and commercialization. This review confirms the potential of intrinsic stimuli‐responsive nanocarriers for enhanced drug delivery and antibacterial killing. This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Infectious Disease Nanotechnology Approaches to Biology > Nanoscale Systems in Biology Abstract : Intrinsic stimuli‐responsive nanocarriers have gained significant interest in the antibacterial research field. In this review, we discuss the potential of these nanocarriers for improved antibacterial drug delivery and highlight further research required to optimize their potential.